How well do healthcare professionals know of the priorities of their older patients regarding treatment outcomes?. Issue 9 (September 2021) - Festen, Suzanne; Stegmann, Mariken E.; Prins, Annemiek; van Munster, Barbara C.; van Leeuwen, Barbara L.; Halmos, Gyorgy B.; de Graeff, Pauline; Brandenbarg, Daan
Highlights: For shared decision making, it is crucial to identify patients' priorities. It was unknown whether healthcare professionals know their patients priorities. In our study healthcare professionals had poor knowledge of these priorities. Agreement was equally poor for general practitioners and medical specialists. Priorities should be explicitly discussed with patients. Abstract: Objectives: For shared decision making, it is crucial to identify patients' priorities regarding health outcomes. Our aim was to study whether healthcare professionals know these priorities. Methods: In this cross-sectional study we included older patients who had to make a treatment decision, their general practitioners (GPs) and their medical specialists. Agreement between the patients' main health outcome as prioritised by using the Outcome Prioritization Tool (OPT) and the perception of the same outcome by their healthcare professionals. Results: Eighty-seven patients were included. Median age was 76 years, 87.4% of patients presented with malignant disease. The majority prioritised maintaining independence (51.7%), followed by extending life (27.6%). The agreement between patients and healthcare professionals was low (GPs 41.7%, kappa 0.067, p = 0.39), medical specialists 40.3%, kappa 0.074, p = 0.33). Positively related to agreement was patient's age > 75, and a longer relation with their patients (for GPs), and the patient having no partner (for medical specialist). Having a malignant disease, dependent living and functional deficits were negatively related to agreement. Conclusions: Healthcare professionals have poor perceptions of their patients' priorities. Practice implications: To realise patient-centered care, it is crucial to discuss priorities explicitly with all patients.